Engagement féminin en Kabylie et intersection des revendications (1980-2001). Dominations, expériences et négociations identitaires - Margherita Rasulo (L’Année du Maghreb)
This article aims to understand the conditions of emergence of the female associative fabric in Kabylia from the 1980s to the 2000s, as well as the modalities and effects of the female presence on the frameworks of civil society and Berber identity movements. It is based on a corpus of archives and interviews. The data come from public and private archives, and from interviews conducted during a survey between November 2018 and January 2019 in the wilaya of Tizi Ouzou and the city of Béjaïa, Algeria. The choice of Kabylia implies a specific contextualisation in Algeria. As subalterns within a minority group, the representatives of this movement are confronted by various processes of minimisation. Kabylia is a Berber-speaking region characterised by the tension between the perpetuation and renegotiation of social and symbolic structures. In this context, the exclusion of women from decision-making spaces, of which the tajmaεt (village assembly) is the main social institution, as well as the existence of female activism in the region, reflect the tension between the perpetuation and the modernisation of the symbolic apparatus, of social structures and, consequently, of gender relations. From a methodological point of view, with regard to its object and geographical context, this work relies on a hybrid theoretical approach that combines Berber/Amazigh studies (Abrous, 1988, 1995, 2004; Chaker, 1988, 1998; Tilmatine, 1989, 2017; Ould Fella, 2021), Kabyle ethnology studies (Bourdieu, 1998; Lacoste-Dujardin, 1985, 2008) and the experiential approach to the minority condition (Chassain et al., 2016), gender studies and subaltern studies (Spivak, 1988). Particular attention is given to the association Tiɣri n’Ttmeṭṭut, active from 1989 to 1995, and the Black Spring Women’s Collective, active since 2001.The hypothesis of the article is that women’s movements and identity movements are part of a relationship of both tension and complementarity, with each generating reciprocal consequences, the scope of which we try to measure in particular for women, who are minoritised among the minorities. This double minoritisation translates into their marginalisation in social reality and their invisibility in the theoretical frameworks of knowledge and knowledge construction, as a result of historical and social factors. This is why women’s activism is an interesting perspective from which to analyse permanence and change in gender relations in the social reality of Kabyle protest movements during the 20th and 21st centuries. By going beyond the historical invisibility of the Kabyle women’s movement, this approach allows us to detect a process, non-linear in its evolution and still under construction, of change and evolution of gender relations that is reflected in the renegotiation of gender identities and the intersection of the claims of those studied.What these movements have in common is that, since the country’s independence, they have been confined by the state to the status of minority groups. The definition of a monolithic Arab and Muslim identity by the central power has in fact led to the undermining of two population groups: Berber speakers and women. We first explain how the state placed the Kabyle identity movements and the women’s movements in a minority position and how the struggles of these actors were organised in parallel or intertwined. In the 1980s and 1990s, the state’s confinement was followed by powerful interactions between the women’s movement in Kabylia and the movement for Kabyle cultural demands. The processes of definition and negotiation of identity by women’s associations were expressed through a dialectical movement of appropriation and contestation of identity claims and gender identities with reference to social, legal and customary normative frameworks. At the same time, women’s and feminist claims were questioned within Kabyle identity associations. However, the revival of women’s specific demands remained extremely limited and even regressed from 2001 onwards. The “Black Spring” led to a reaffirmation of the patriarchal system, including in the structuring of the protest movement of this period.